Iron metabolism, hepcidin, and mortality (the Ludwigshafen Risk and Cardiovascular Health Study) - Grammer, Tanja B.; Scharnagl, Hubert; Dressel, Alexander; Kleber, Marcus E.; Silbernagel, Günther; Pilz, Stefan; Tomaschitz, Andreas; Koenig, Wolfgang; Mueller-Myhsok, Bertram; März, Winfried; Strnad, Pavel (Clinical chemistry, 2019)
Background: Anemia has been shown to be a risk factor for coronary artery disease (CAD) and mortality, whereas the role of iron metabolism remains controversial. Methods: We analyzed iron metabolism and its associations with cardiovascular death and total mortality in patients undergoing coronary angiography with a median follow-up of 9.9 years. Hemoglobin and iron status were determined in 1480 patients with stable CAD and in 682 individuals in whom significant CAD had been excluded by angiography. Results: Multivariate-adjusted hazard ratios (HRs) for total mortality in the lowest quartiles of iron, transferrin saturation, ferritin, soluble transferrin receptor (sTfR), and hemoglobin were 1.22 (95% CI, 0.96-1.60), 1.23 (95% CI, 0.97-1.56), 1.27 (95% CI, 1.02-1.58), 1.26 (95% CI, 0.97-1.65), and 0.99 (95% CI, 0.79-1.24), respectively, compared to the second or third quartile, which served as reference because of a J-shaped association. The corresponding HRs for total mortality in the highest quartiles were 1.44 (95% CI, 1.10-1.87), 1.37 (95% CI, 1.05-1.77), 1.17 (95% CI, 0.92-1.50), 1.76 (95% CI, 1.39-2.22), and 0.83 (95% CI, 0.63-1.09) compared to the second quartile. HRs for cardiovascular death were similar. For hepcidin, the adjusted HRs for total mortality and cardiovascular deaths were 0.62 (95% CI, 0.49-0.78) and 0.70 (95% CI, 0.52-0.90) in the highest quartile compared to the lowest one. Conclusions: In stable patients undergoing angiography, serum iron, transferrin saturation, sTfR, and ferritin had J-shaped associations and hemoglobin only a marginal association with cardiovascular and total mortality. Hepcidin was continuously and inversely related to mortality.